2010
DOI: 10.21273/jashs.135.1.49
|View full text |Cite
|
Sign up to set email alerts
|

The Dominant Ms Allele in Onion Shows Reduced Penetrance

Abstract: The most commonly used source of cytoplasmic male sterility in onion (Allium cepa) is controlled by the interaction of the cytoplasm [male-sterile (S) or normal male-fertile (N)] and one nuclear male-fertility-restoration locus (Ms). Scoring of genotypes at Ms is generally done by testcrossing male-fertile to male-sterile (S msms) plants, followed by scoring of testcross progenies for male-fertil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…For AC, frequencies of male fertile plants in testcross families carrying the dominant Ms allele agreed with predictions of the AcPms1 marker. However significantly lower pollen stainability was observed relative to Ski (Table 1), consistent with reduced penetrance of the dominant Ms allele from AC, as previously reported by Melgar and Havey (2010). Male sterility in inbred B2354A has been problematic across many seed production cycles.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…For AC, frequencies of male fertile plants in testcross families carrying the dominant Ms allele agreed with predictions of the AcPms1 marker. However significantly lower pollen stainability was observed relative to Ski (Table 1), consistent with reduced penetrance of the dominant Ms allele from AC, as previously reported by Melgar and Havey (2010). Male sterility in inbred B2354A has been problematic across many seed production cycles.…”
Section: Resultssupporting
confidence: 85%
“…AC43 was crossed as the male with BYG15-23 (N-cytoplasmic and homozygous recessive at Ms) and a segregating F 2 family was developed (King et al, 1998). F 2 progenies were self-pollinated and testcrossed to Scytoplasmic male sterile plants, and one F 3 family (USDA breeding plot 16278) homozygous dominant at Ms was selected and used by Melgar and Havey (2010) for three generations, producing an inbred (AC) that possesses S cytoplasm and is heterozygous at Ms (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study with Indian germplasm, Khar and Saini (2016) reported a low agreement between the markerassisted selection of 'A' and 'B' lines with viability test with 0.5% acetic carmine. The low agreement reported by the authors mentioned above may be related to the reduced penetrance of the Ms allele reported by Melgar and Havey (2010), in which plants homozygous dominant at Ms may not present 100% fertility restoration, suggesting not a failure of the marker-assisted selection. In the present study, agreement was observed for the classification by the pollen viability methods employed with assisted selection for the plants of seven accessions and absence of agreement for plants of five accessions, indicating reasonable accuracy of the assisted selection.…”
Section: Discussionmentioning
confidence: 86%
“…However, as recently as 2010, Melgar and Havey (2010) have confirmed that the dominant Ms allele can show reduced penetrance, requiring that male-fertility restoration be scored over years to confidently assign genotypes at Ms. Male-sterile plants have composition S-msms, the thermostabile sterility (no pollen under high temperatures) resulting from premature breakdown of the tapetum.…”
Section: The Use Of Cms-s In Hybrid Onion Breedingmentioning
confidence: 99%